Status of Dwarf Mistletoe (Arceuthobium minutissimum Hook. f.) on Blue Pine in Jammu & Kashmir - Shukla, A. N.; Singh, Y. P. (Indian Forester, 2007)
Blue pine (Pinus wallichiana A.B. Jackson) which occurs naturally in the temperate zone of Central and Western Himalayas, is attacked by dwarf mistletoe. It is a disease of low rainfall area and known only from Western Himalayas in Pakistan, Jammu & Kashmir in India and Nepal. A survey was conducted in 2005-2006 in different forest divisions of Kashmir Valley and Jammu. Symptoms and disease intensity were recorded in different girth classes of Blue pine. In young plants, spindle shaped swellings in the infected branches was the most prominent symptom. Mature tree showed deformity of branches and poor crown. There was a linear relationship between increasing girth and disease intensity, for example, only 48 per cent infection was recorded in < 30 cm girth class, while 100 per cent trees were infected in 111-200 cm girth class and above.